Ionic liquid modified MOF gel mixed matrix membrane for efficient carbon dioxide separation as well as preparation method and application of ionic liquid modified MOF gel mixed matrix membrane

By combining the ionic liquid-modified MOF gel material with polymer matrix to form IL@MOF gel MMMs, the selectivity and stability of traditional membrane materials in CO2 capture concentration is solved, and the permeability and selectivity of CO2 are significantly improved. , and improves mechanical properties and is suitable for large-scale production.

CN119258737APending Publication Date: 2025-01-07HUNAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411447883.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional membrane materials have limitations in gas selectivity, permeability flux and long-term stability in CO2 capture concentration, and the compatibility between MOF materials and polymers is poor, resulting in unstable mechanical properties and gas separation properties of the membrane.

Method used

A metal organic frame (MOF) gel material modified with ionic liquid is used to form a mixed matrix membrane (IL@MOF gel MMMs) by combining the ionic liquid with the MOF gel material to improve the gas separation performance and mechanical strength of the membrane.

Benefits of technology

It significantly improves the selective adsorption capacity and permeability of CO2, improves the mechanical properties and stability of the membrane, and maintains excellent separation performance during long-term use, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119258737A_ABST
    Figure CN119258737A_ABST
Patent Text Reader

Abstract

The invention provides an ionic liquid modified MOF gel (MOF gel) mixed matrix membrane (MMMs) for efficient carbon dioxide separation and a preparation method thereof. The ionic liquid and the MOF gel material are combined, and the gas separation performance of the membrane is remarkably improved through the synergistic effect of the ionic liquid and the MOF gel material. The ionic liquid has high polarity and selective adsorption capacity on CO2, so that the CO2 permeability and selectivity of the membrane are greatly improved. Meanwhile, the three-dimensional interconnection network structure of the MOF gel enhances the dispersity of the material, constructs a continuous penetrating channel, effectively promotes gas transmission, and improves the long-term stability of the film. After the two are combined, the membrane material not only has a more excellent gas separation effect, but also has mechanical strength and operation stability. The preparation method is simple and convenient to operate, is suitable for large-scale industrial production, has the advantages of energy conservation and environmental protection, and particularly has wide application potential in the field of carbon dioxide capture and separation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane separation, and in particular to a mixed matrix membrane (MMMs) prepared by an ionic liquid-modified metal organic framework (MOF) gel and a method for using the mixed matrix membrane (MMMs) in CO2 capture. Background Art

[0002] With the continuous increase of industrial production and energy consumption, excessive CO2 emissions have become one of the main causes of global climate change. CO2 capture and storage (CCS) technology is an important means to deal with this problem, and membrane separation technology has become one of the important methods for CO2 capture due to its advantages such as low energy consumption, compact equipment, simple operation, and continuous operation. However, traditional membrane materials, such as polymer membranes and inorganic membranes, have obvious limitations in gas selectivity, permeation flux, and long-term stability, and are difficult to meet industrial needs in practical applications.

[0003] Metal-organic framework (MOF) materials have become a hot topic in gas separation membrane research in recent years due to their unique pore structure, adjustable pore size and high specific surface area. MOF materials have good gas adsorption capacity, especially showing great potential in the capture and separation of CO2. However, traditional MOF membranes are prone to particle aggregation and uneven distribution in polymer matrices, and the compatibility between MOF materials and polymers is poor, resulting in unstable mechanical properties and gas separation performance of the membrane. To solve these problems, MOF gel (MOF gel) was introduced as a new type of material. MOF gel is composed of MOF nanoparticles (MOF precursors) through non-covalent forces to form a three-dimensional interconnected network structure with end-to-end connection. It has higher flexibility and better dispersibility and stability in the solution, making it easier to be evenly distributed in the polymer matrix and form continuous channels, so that MOF gel MMMs show higher gas permeability.

[0004] Although MOF gel can improve the dispersibility and compatibility of membrane materials, its application in MMMs still faces challenges in compatibility and long-term stability. For this reason, ionic liquids (ILs), as highly polar compounds with specific adsorption properties for CO2, are gradually being considered as effective additives to enhance membrane separation performance. ILs can not only improve the dispersibility and compatibility of MOF materials in polymer matrices by interacting with their surfaces, but also improve the permeability and selectivity of CO2. Therefore, by introducing IL-modified MOF gel materials into MMMs, the compatibility and stability problems in the prior art can be effectively solved, further improving the comprehensive performance of the membrane and the efficiency of CO2 capture. Summary of the invention

[0005] The purpose of the present invention is to provide an IL@MOF gel MMMs membrane, which has high CO2 separation performance and a simple preparation method and is suitable for large-scale production.

[0006] To achieve the above object, the specific technical solutions of the present invention are as follows:

[0007] Step (1): weigh 0.2-0.5 g of ionic liquid, dissolve it in 30 mL of chloroform, and stir for 1 hour to obtain a uniform ionic liquid solution;

[0008] Step (2): preparing a 0.13-0.53 mol / L metal ion solution using methanol as a solvent, and preparing an organic ligand solution according to a ratio of metal ion: imidazole: triethylamine of 1:8:8;

[0009] Step (3): Mix and stir the organic ligand solution for 10 to 60 minutes. Wash the unreacted ligand three times with chloroform to obtain MOF gel, which is then redispersed in chloroform to form a MOF gel chloroform suspension;

[0010] Step (4): The two solutions were mixed and stirred for 24 hours at a mass ratio of IL to MOF gel = 1:1. After stirring, the two solutions were washed three times with chloroform to remove the free ionic liquid.

[0011] Step (5): dissolving an appropriate amount of polymer in an organic solvent to obtain a polymer solution, then adding a certain amount of the polymer solution dropwise to the IL@MOFgel, ultrasonicating and stirring until the two are evenly mixed to form a casting mixed solution, pouring the solution into a smooth and flat round glass culture dish, slowly evaporating at room temperature for 1 to 4 days, and finally drying the film in a vacuum oven at 80 to 120°C for 12 to 24 hours to obtain IL@MOF gel MMMs.

[0012] In step (1) of the present invention, the ionic liquid can be selected from 1-ethyl-3-methylimidazolium dicyanamide ([EMIM][N(CN)2]), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ([EMIM][Tf2N]) or 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM][BF4]). In step (2) of the present invention, the metal ion solution may be Zn 2+ or Co 2+ .

[0013] In step (4) of the present invention, the polymer may be selected from polyimide, self-polymerizing microporous polymer, polybenzimidazole and the like.

[0014] In step (5) of the present invention, the content of the IL@MOF gel is 1 to 40 wt % of the mass of the IL@MOF gel MMMs.

[0015] In step (5) of the present invention, the total mass concentration of the polymer and IL@MOF gel in the mixed solution for casting the membrane is 1.5 to 3.0 wt%.

[0016] Preferably, the solvent of the film casting mixed solution is selected from chloroform and N,N-dimethylformamide.

[0017] In step (5) of the present invention, the stirring time is 12 to 24 hours.

[0018] In step (5) of the present invention, the treatment temperature of the vacuum treatment is 80 to 150° C., and the treatment time is 12 to 24 hours.

[0019] According to one aspect of the present invention, there is provided a use of the above-mentioned IL@MOF gel MMMs in gas separation.

[0020] Optionally, the IL@MOF gel MMMs are used in the separation of a mixture containing CO2.

[0021] Preferably, the gas comprises at least one of N2 and CH4.

[0022] In the present application, the gas mixture contacts one side of the IL@MOF gel MMMs, thereby causing CO2 to permeate the IL@MOF gel MMMs to achieve a gas separation effect.

[0023] Compared with the prior art, the present invention has the following beneficial technical effects:

[0024] The IL@MOF gel MMMs of the present invention are prepared by combining an ionic liquid-modified MOF gel material with a polymer matrix, which significantly improves the gas separation performance of the membrane. By introducing the ionic liquid, the compatibility of the MOF gel material with the polymer matrix is ​​enhanced, forming a more uniform dispersed structure, thereby greatly improving the selective adsorption capacity and permeability of CO2. At the same time, the unique properties of the ionic liquid help to improve the mechanical strength and stability of the membrane, so that it maintains excellent separation performance during long-term use.

[0025] The film-making method provided by the invention is easy to operate, has strong applicability, is suitable for large-scale production, is environmentally friendly and energy-saving, and has broad industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the XRD pattern of IL@MOF gel in Example 1-3.

[0027] Figure 2 This is the Fourier infrared image of the IL@MOF gel in Example 1-3.

[0028] Figure 3 This is the nitrogen adsorption diagram of IL@MOF gel in Examples 1-3.

[0029] Figure 4 This is the micropore distribution diagram of IL@MOF gel in Examples 1-3.

[0030] Figure 5 CO2 adsorption diagram of IL@MOF gel in Examples 1-3.

[0031] Figure 6 These are Fourier infrared images of the films prepared in Examples 1-3 and Comparative Examples 1 and 2.

[0032] Figure 7 The XRD patterns of the films prepared in Example 1 and Comparative Examples 1 and 2 are shown below.

[0033] Figure 8 Gas separation performance of the membranes prepared in Examples 1, 4-6 and Comparative Examples 1-5.

[0034] Fig. 9 The figure is a comparison chart of the gas separation performance of the membranes prepared in Examples 1, 4-6.

[0035] Fig.10 The mass transfer model fitting diagram of the gas separation performance of the membranes prepared in Examples 1, 4-6 and Comparative Examples 1-5. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below through several specific embodiments, but the present application is not limited thereto. Without departing from the content and scope of the present invention, any changes and implementations should be included in the technical scope of the present invention.

[0037] Example 1:

[0038] Step (1): Weigh 0.5 g of 1-ethyl-3-methylimidazolium dicyanamide ([EMIM][N(CN)2]) ionic liquid, dissolve it in 30 mL of chloroform, and stir for 1 hour to obtain a uniform ionic liquid solution;

[0039] Step (2): preparing a 0.53 mol / L metal ion solution using methanol as a solvent, and preparing an organic ligand solution according to a ratio of metal ion: imidazole: triethylamine of 1:8:8;

[0040] Step (3): Mix and stir the organic ligand solution for 60 minutes. Wash the unreacted ligand three times with chloroform to obtain MOF gel, which is then redispersed in chloroform to form a MOF gel chloroform suspension;

[0041] Step (4): The two solutions were mixed and stirred for 24 hours at a mass ratio of IL to MOF gel = 1:1. After stirring, the two solutions were washed three times with chloroform to remove the free ionic liquid, and finally redispersed in chloroform to prepare a [EMIM][N(CN)2]@MOF gel mixed solution.

[0042] Step (5): 0.2 g of self-polymerized microporous polymer (PIM-1) was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.02 g of [EMIM][N(CN)2]@MOF gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the membrane was placed in a vacuum oven at 80°C and dried for 24 hours to obtain 9.0 wt% [EMIM][N(CN)2]@ZIF-8gel / PIM-1MMMs.

[0043] Example 2:

[0044] Step (1): Weigh 0.5 g of 1-ethyl-3-methylimidazolium-bis(trifluoromethanesulfonyl)imide ([EMIM][Tf2N]) ionic liquid, dissolve it in 30 mL of chloroform, and stir for 1 hour to obtain a uniform IL solution;

[0045] Steps (2)-(3) are the same as in Example 1

[0046] Step (4): The two solutions were mixed and stirred for 24 hours at a mass ratio of IL to MOF gel = 1:1. After stirring, the two solutions were washed three times with chloroform to remove the free ionic liquid, and finally redispersed in chloroform to prepare a [EMIM][Tf2N]@MOF gel mixed solution.

[0047] Step (5): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.02 g of [EMIM][Tf2N]@MOF gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 80°C and dried for 24 hours to obtain 9.0 wt% [EMIM][Tf2N]@ZIF-8gel / PIM-1MMMs.

[0048] Example 3:

[0049] Step (1): Weigh 0.5 g of 1-butyl-3-methylimidazolium-tetrafluoroborate ([BMIM][BF4]) ionic liquid, dissolve it in 30 mL of chloroform, and stir for 1 hour to obtain a uniform IL solution;

[0050] Steps (2)-(3) are the same as in Example 1;

[0051] Step (4): Mix and stir the two solutions for 24 hours in a mass ratio of IL to MOF gel = 1:1. After stirring, wash the two solutions three times with chloroform to remove the free ionic liquid, and finally redisperse them in chloroform to prepare a [BMIM][BF4]@MOF gel mixed solution.

[0052] Step (5): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.02 g of [BMIM][BF4]@MOF gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the membrane was placed in a vacuum oven at 80°C and dried for 24 hours to obtain 9.0 wt% [BMIM][BF4]@ZIF-8gel / PIM-1MMMs.

[0053] Example 4:

[0054] Steps (1) to (4) are the same as in Example 1;

[0055] Step (5): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.04 g of [EMIM][N(CN)2]@MOF gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 80°C and dried for 24 hours to obtain 17.0 wt% [EMIM][N(CN)2]@ZIF-8gel / PIM-1MMMs.

[0056] Example 5:

[0057] Steps (1) to (4) are the same as in Example 1;

[0058] Step (5): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.06 g of [EMIM][N(CN)2]@MOF gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 80°C and dried for 24 hours to obtain 23.0 wt% [EMIM][N(CN)2]@ZIF-8gel / PIM-1MMMs.

[0059] Example 6:

[0060] Steps (1) to (4) are the same as in Example 1;

[0061] Step (5): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.08 g of [EMIM][N(CN)2]@MOF gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the film was placed in a vacuum oven at 80°C and dried for 24 hours to obtain 28.0 wt% [EMIM][N(CN)2]@ZIF-8gel / PIM-1MMMs.

[0062] Comparative Example 1:

[0063] Dissolve 0.2 g of PIM-1 in chloroform, stir at room temperature for 24 hours to form a casting solution, pour it into a smooth and flat round glass Petri dish, slowly evaporate at room temperature for 2 days, then soak the membrane in methanol for 1 day, and finally place the membrane in a vacuum oven at 80°C and dry it for 24 hours to obtain pure PIM-1MMM.

[0064] Comparative Example 2:

[0065] Step (1): preparing a 0.53 mol / L metal ion solution using methanol as a solvent, and preparing an organic ligand solution according to a ratio of metal ion: imidazole: triethylamine of 1:8:8;

[0066] Step (2): The organic ligand solution was mixed and stirred for 60 minutes. The unreacted ligand was washed three times with chloroform to obtain MOF gel, which was then redispersed in chloroform to form a ZIF-8gel chloroform suspension;

[0067] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.02 g of ZIF-8gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the membrane was placed in a vacuum oven at 80°C and dried for 24 hours to obtain 9.0 wt% MOF gel MMMs.

[0068] Comparative Example 3:

[0069] Step (1) to step (2) are the same as in Comparative Example 2;

[0070] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.04 g of ZIF-8gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the membrane was placed in a vacuum oven at 80°C and dried for 24 hours to obtain 17.0 wt% ZIF-8gel MMMs.

[0071] Comparative Example 4:

[0072] Step (1) to step (2) are the same as in Comparative Example 2;

[0073] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.06 g of ZIF-8gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the membrane was placed in a vacuum oven at 80°C and dried for 24 hours to obtain 23.0 wt% ZIF-8gel MMMs.

[0074] Comparative Example 5:

[0075] Step (1) to step (2) are the same as in Comparative Example 2;

[0076] Step (3): 0.2 g of PIM-1 was dissolved in chloroform to obtain a polymer solution, and then a certain amount of the polymer solution was dropwise added to a solution containing 0.08 g of ZIF-8gel, and the two were ultrasonically stirred until they were evenly mixed to form a casting mixed solution, which was poured into a smooth and flat round glass culture dish and slowly evaporated at room temperature for 2 days. Finally, the membrane was placed in a vacuum oven at 80°C and dried for 24 hours to obtain 28.0 wt% ZIF-8gel MMMs.

[0077] The CO2 permeability and selectivity of the MMMs in Examples 1-6 and Comparative Examples 1-5 at 0.1 MPa and 35°C when the gas mixture is CO2 / CH4 are shown in Table 1.

[0078] From the data, it can be seen that cyanide plays a key role in improving the gas separation performance of membrane materials, especially through the introduction of [EMIM][N(CN)2], a cyanide-containing ionic liquid, which significantly improves the gas separation performance of PIM-1MMMs. Specifically, with the increase in the doping amount of [EMIM][N(CN)2]@ZIF-8gel, the CO2 permeability coefficient gradually increases from 3857 Barrer at 9.0wt% to 9410 Barrer at 28.0wt%, and the CO2 / CH4 selectivity also increases from 19.9 to 28.9. Compared with other ionic liquids such as [EMIM][Tf2N] and [EMIM][BF4], [EMIM][N(CN)2] performs better, indicating that the cyanide (CN) group has a significant enhancing effect on the gas permeability and selectivity of the membrane. The high polarity and small size of the cyanide group enable it to better interact with the active sites in the ZIF-8gel structure, thereby forming a more effective gas permeation channel in the membrane. Especially for CO2 molecules, cyano groups can form stronger interactions with CO2 molecules through their polarity, thereby promoting the transmission of CO2. At the same time, since the interaction of cyano groups with other gas molecules (such as CH4) is relatively weak, while enhancing the CO2 permeability, it can also significantly improve the CO2 / CH4 selectivity. This differentiated interaction mechanism is the key reason why cyano groups can effectively improve gas separation performance. In summary, in MMM, [EMIM][N(CN)2] plays an important role, greatly improving the CO2 permeability and selectivity of the membrane, enabling it to exhibit excellent gas separation performance at high doping levels (28.0wt%). The introduction of cyano groups is obviously an important strategy to improve the gas separation efficiency of membrane materials, especially in applications involving CO2 separation. It has significant advantages.

[0079] The above are only several embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, using the above disclosed technical content to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. An ionic liquid (IL) modified MOF gel (MOF gel) mixed matrix membrane (MMMs) for efficient carbon dioxide separation and its preparation method and application, characterized in that: The IL@MOF gel MMMs comprises a polymer matrix and IL@MOFgel; The IL@MOF gel is a MOF gel and an IL adsorbed on its surface; The MOF gel is selected from zinc MOF gel and cobalt MOF gel.

2. The IL@MOF gel MMMs according to claim 1, characterized in that: The zinc MOF gel is selected from ZIF-8gel; Preferably, the cobalt-based MOF gel is ZIF-67gel.

3. The IL@MOF gel MMMs according to claim 1, characterized in that: The content of the IL@MOF gel is 1 wt% to 40 wt% of the mass of the IL@MOF gel MMMs.

4. The IL@MOF gel MMMs according to claim 1, characterized in that: The polymer matrix is ​​selected from at least one of polyimide, polybenzimidazole and self-polymerizing microporous polymer.

5. A method for preparing the IL@MOF gel MMMs according to any one of claims 1 to 4, characterized in that: The IL@MOF gel MMMs are obtained by forming a film from a mixed solution containing a polymer and IL@MOF gel and subjecting the film to vacuum treatment.

6. The preparation method according to claim 5, characterized in that: After mixing the solution a containing the polymer with the solution b containing the IL@MOFgel, the casting film mixed solution is obtained; The stirring time is 12 to 24 hours.

7. The preparation method according to claim 5, characterized in that: In the mixed solution for casting the membrane, the total mass concentration of the polymer and the IL@MOF gel is 1.5-3wt%; Preferably, the solvent of the film casting mixed solution is selected from at least one of chloroform and N,N-dimethylformamide.

8. The preparation method according to claim 5, characterized in that: The treatment temperature of the vacuum treatment is 80-150° C., and the treatment time is 24-48 hours.

9. Use of the IL@MOF gel MMMs according to any one of claims 1 to 4 or the IL@MOF gel MMMs prepared by the preparation method according to any one of claims 5 to 8 in gas separation.

10. The use according to claim 9, characterized in that: Application of the IL@MOF gel MMMs in separation of gas mixtures containing CO2; Preferably, the gas comprises at least one of N2 and CH4.

Citation Information

Patent Citations

  • Preparation and application of high-performance mixed matrix gas separation membrane based on ionic liquid coordination

    CN116351265A

  • Metal organic framework gel mixed matrix membrane as well as preparation method and application thereof

    CN117443208A